A critical success factor model for CRM implementation - da Silva, R. V.; Rahimi, I. (International Journal of Electronic Customer Relationship Management, 2007)
Customer Relationship Management (CRM) implementation has been a daunting and exhaustive experience for many organisations. Managers and decision makers find that there is no one ‘fixed formula’ to guarantee its success. This paper draws from CSF models in ERP implementation and project management, determining their applicability to successful CRM implementation in a B2B context. Eight (8) companies who implemented CRM were scrutinised, in which overlapping issues with ERP Implementation and project management were analysed. This analysis was the foundation of a CSF model for CRM implementation, providing a list of strategic and tactical CSFs that are present when undergoing such a process.